Do forecasters inform or reassure? Evaluation of the German real-time data - Konstantin A. Kholodilin; Boriss Siliverstovs (ETH Zurich, KOF Swiss Economic Institute, 2009)
The paper evaluates the quality of the German national accounting data (GDP and its use-side components) as measured by the magnitude and dispersion of the forecast/revision errors. It is demonstrated that government consumption series are the least reliable, whereas real GDP and real private consumption data are the most reliable. In addition, early forecasts of GDP, private consumption, and investment growth rates are shown to be systematically upward biased. Finally, early forecasts of all the variables seem to be no more accurate than naïve forecasts based on the historical mean of the final data.
Keywords: C53; C89; 330; Quality of statistical data; real-time data; signal-to-noise ratio; forecasts; revisions; Konjunkturprognose; Prognoseverfahren; Statistischer Fehler; Volkswirtschaftliche Gesamtrechnung; Statistik; Informationswert; Deutschland